HUBUNGAN KECANDUAN BERMAIN GAME ONLINE TERHADAP REGULASI EMOSI PADA REMAJA - Anita Nurazmi; Veny Elita; Wan Nisfha Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Online game is an internet-based game connected by the internet so it can be played by many players and can affect the players' emotional regulation as it forgets the real world activity as it is only focused on playing games. The main focus of this research was to investigate whether there was a significant relationship between online gaming addiction and emotion regulation of adolescence. This research use descriptive correlational design with cross sectional approach. This study was conducted on 267 samples selected based on inclusion criteria with proportionate stratified random sampling technique. The instrument of this study was a questionnaire which had been modified and examined by validity and reliability tests. The result showed that the majority of respondents are young middle age (15-17 years of age) of 250 respondents (93,6%), most of them were males 235 respondents (88,0%), the mean of respondents who were playing games in 7-9 hours per day was 96 respondents (59,3%). Respondents who were addicted by online games were 107 respondents (40,1%). Respondents who had low emotion regulation were 121 respondents (54,7%). Bivariate analysis with Chi-square test showed p value 0,000 < 0,05. It mean’s that is a relationship between online game addiction and emotion regulation of adolescence. The result findings recommended the adolescence to manage their time and to control them selves in playing online game so that no impact on emotional regulation.Keyword: Adolescents, emotion regulation, online game.